Minat Masyarakat Kota Bekasi Terhadap Pembiayaan Talangan Haji Pada Perbankan Syariah (Analisis Pada PT. Bank Syariah Mandiri KCP Bekasi Timur) - Aan Riyadi; Isfandayani - (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2019)
This research is motivated by the role of Islamic banks in distributing hajj bailout products.The role of Sharia Banks targeting Hajj bailout products increasingly indicates the public’s need forIslamic banking. This research raises the title of Bekasi City Public Interest in Hajj Bailout Financingin Islamic Banking. The objectives and limitations of the problem in this study are how the procedurefor implementing haj bailout financing at BSM KCP East Bekasi, the interest of the Bekasi Citycommunity towards haj bailout financing, and how the Business of Bank Syariah Mandiri KCP EastBekasi attracts the public’s interest in providing haj bailout fees. used in this research is qualitative.This research was collected using observation, interviews with the head of microfinance at BSM KCPEast Bekasi. The approach used is descriptive to find out information from the informants on the hajjbailout financing process at BSM KCP Bekasi Timur. Based on the research results, the procedureof Bank Syariah Mandiri KCP Bekasi Timur has established a mechanism for the portion of hajjfor customers who need Hajj bailout financing, and the portion is divided into two, namely for cashportions and bailouts. Registration of the cash hajj portion is a portion that can be said is simplerthan the portion of the bailout hajj. While the interest of the Bekasi City community can be seen thatof the total population of Bekasi City of 2,376,794, 2,145,497 are Muslims, the total is 2,145,497only 990,630. souls who are required to perform the pilgrimage. The pilgrims who departed in 2014were dominated by Islamic banking as many as 1,407 people (58.4%), while conventional banks were1,002 people (41.6%). Of the several Sharia Banks, including Bank Syariah Mandiri (BSM) KCP EastBekasi, it was able to take the portion of the pilgrims as many as 608 people. Bank Syariah Mandiri’sefforts in attracting haj bailouts include collaborating with several local Hajj Guidance Groups(KBIH) and then by distributing mabrur savings brochures along with the haj registration process andthe Bank Syariah Mandiri haj bailout program, East Bekasi KCP to customers and telemarketing andsocialization by holding seminars on haj bailout financing.